Difference in Sodium and Potassium Reading by Blood Gas Analyzer and Electrolyte Analyzer at Sanglah Hospital Denpasar, Bali, Indonesia - Anak Agung Wiradewi Lestari; I Putu Sidhi Rastu Karyana; I Nyoman Wande (Journal of Global Pharma Technology, 2018)
Introduction: Electrolytes measurement is a standard procedure in medical practice to diagnose diseases or disease-related complication. Recently, there is a various device used to analyze blood electrolytes, but the difference accuracy between devices is a problematic issue for clinicians. Thus, we evaluate the differences of sodium and potassium concentration reading by Blood Gas Analyzer (BGA) and Electrolyte Analyzer at Sanglah Hospital to assess whether the difference could be accepted according to Clinical Laboratories Improvement Amendments (CLIA). Methods: A cross-sectional analytic study was conducted in May 2017 at Clinical Pathology Laboratory of  Sanglah Hospital, Denpasar. 30 subjects were enrolled consecutively during the study period and the blood samples were analyzed by both BGA and electrolyte analyzer. The data were analyzed using paired T-Test, Bland-Altman Plot, and Linear Regression. Result: The mean of sodium and potassium measured by BGA were 133.76 ± 5.68 mmol/L and 3.14 ± 0,86 mmol/L, respectively while electrolyte analyzer was 136,43 ± 6,48 mmol/L and 3,51 ± 0,9 mmol/L, respectively. Mean difference between sodium and potassium were 2.67 mmol/L (P=0,000) and 0.36 mmol/L (P=0,000), respectively. Bland-Altman plot analysis in sodium and potassium showed that the limit of the agreement was at -9.9 to 4.56 mmol/L and -1.28 to 0.56 mmol/L, respectively. Conclusion: There was a significant difference between BGA and electrolyte analyzer reading with BGA has higher acceptance level compared to electrolyte analyzer.Keywords: Natrium, Kalium, Blood Gas Analyzer, Electrolyte Analyzer.